Research progress and perspectives on the application of tyramide signal amplification-based multiplex immunohistochemistry/immunofluorescence: a bibliometrics analysis - Yu, Xiaotong; Huang, Chen; Song, Yan; Zhang, Chun; You, Debo; Dong, XuRan; Wu, DeFu; Meeker, Alan Keith; Feng, Hao; Wang, Yuqing (Frontiers in Oncology, 2025)
Background and aimsMultiplex immunohistochemistry/immunofluorescence (mIHC/IF), which uses the tyramide signal amplification (TSA) technique, enables sequential staining of multiple targets in formalin-fixed paraffin-embedded (FFPE) samples without worrying about cross-reactivity. This approach has received considerable attention from researchers over the past decades. This article aims to provide a bibliometric analysis of the research progress and perspectives on the application of TSA-based mIHC/IF.MethodsWe collected all the TSA-based mIHC/IF documents published between 2007 and 2023 from the Web of Science Core Collection (WoSCC) database. CiteSpace, VOSviewer and Bibliometrix R Package were used to perform the bibliometrics analysis, including details about annual publications, countries, institutions, authors, journals, and research topics and hotspots.ResultsA total of 873 relevant publications (811 articles and 62 reviews) with a time span of 17 years (2007-2023) were obtained. The number of annual publications started to increase rapidly since 2016. The United States (307, 35.17%) and the People’s Republic of China (297, 34.02%) are the top two listed countries for both the number of articles produced and the citations. The University of Texas System (53, 6.07%) was the most productive institution. Integrating these results of hotspot and frontier analysis, TSA-based mIHC/IF provides significant benefits, particularly in neurology, cancer and immunology.ConclusionThis study conducted a comprehensive bibliometric analysis for the use of TSA-based mIHC/IF. As TSA-based mIHC/IF and its associated imaging systems and analytic software progress, it will become the most promising tool for describing the variety of the whole tissue for a better understanding of pathological or physiological behavior.